Navigating Digital Transformation: Challenges and Strategies for Islamic Religious Education Teachers in Elementary Schools - Andriyan Veisyal Seftiana Putra; Endi Suhendi (UIN Sunan Gunung Djati Bandung, 2026)
The transformation of Islamic Religious Education (PAI) learning in the digital era presents complex challenges for Elementary School teachers, especially in the PAI Teacher Working Group in Babakan Cikao, Purwakarta Regency. This study aims to identify these challenges and explore effective strategies to overcome them, with a focus on increasing teacher commitment to teaching and utilizing 21st-century learning elements, as applied in teaching the Quran. A descriptive qualitative research method was used to explore teachers' experiences and perspectives in depth, focusing on a case study in the Islamic Religious Education Teacher Working Group in Babakan Cikao, Purwakarta Regency; Data were collected through in-depth interviews, classroom observations, and document analysis related to the implementation of PAI learning in the digital era, to be analyzed comprehensively to identify key themes and patterns relevant to the research objectives. This study is expected to provide practical contributions to the professional development of PAI teachers, curriculum improvement, and improving the quality of PAI learning that is adaptive to the demands of the digital era. The results of the study indicate that the challenges faced by teachers in transforming PAI learning in the digital era include adapting to changing curricula, limited digital resources, and improving teachers' competency in using technology. The strategies implemented by the Babakan Cikao District Islamic Religious Education Working Group (KKG PAI) to improve the quality of Islamic Religious Education learning in the digital era include training and workshops on technology utilization, development of interactive learning media, and collaboration with relevant parties to provide relevant and high-quality digital resources.